Contemporary Treatment of Pulmonary Embolism: Medical Treatment and Management - Moreland, Stephen; Mukherjee, Debabrata; Nickel, Nils P. (International Journal of Angiology, 2022)
Pulmonary embolus (PE) is defined as obstruction of the pulmonary artery or one of its branches by material (e.g., thrombus, tumor, air, or fat) but most commonly due to thrombus originating from the lower extremity deep veins.We reviewed the current literature describing the optimal medical treatment and management of PE.Databases (PubMed, the Cochrane Library, Embase, EBSCO, Web of Science, and CINAHL) were searched for relevant studies and guidelines for management of patients with PE.The initial approach to patients with suspected PE should focus upon stabilizing the patient while further workup for risk stratification is in progress. In most cases, anticoagulation should ideally be started even prior to confirming PE, if risk–benefit regarding suspicion of PE and bleeding risk is favorable.Once the diagnosis is confirmed, risk stratification will guide further therapies consisting of anticoagulation, thrombolysis, or catheter-directed interventions. Data for initial, long-term, and indefinite anticoagulation, and factors that determine whether or not a patient can be treated in the outpatient setting, are reviewed and discussed.
Keywords: pulmonary embolism; anticoagulation; thrombolytic; pharmacotherapy; risk stratification